PENGARUH LINTASAN TRAKTOR TANPADAN PEMBERIAN BAHAN ORGANIK TERHADAP PEMADATAN TANAH DAN KERAGAAN TANAMAN KACANG TANAH - Iqbal .; Tineke Mandang; E Namaken Sembiring (PERTETA, 2006)
ABSTRACT The amendment of organic matter into soil can improve the soil condition and prevent soil comaction caused by tractor traffice. The aims of this research are to know the influence or tractor traffic and organic matter on nature of physical mechanic of soil, analyze the influence of tractor traffic and organic matter on performance of soil tillage and to know the influence of soil compaction on performance of peanut crop. This research was conducted in leuwikopo farm (dry land) and in the laboratory for soil analyze. The result show that tractor traffic and organic matter treatmen have effect to soil compaction and performance peanuut crop. The highest value of bulk density is 1.2 g / cm3 at 6 traffic with the organic matter doses 4 ton /ha /hatreatment. The biggest number of pods is 25 pod / tree there is at 2 traffic with pod / tree at 6 traffic without organic matter treatment. Keyword: Tractor traffic, organic matter, soil compaction. Diterima: 27 Pebruari 2006; Disetujui: 23 Juli 2006